Cytogenetic characterization of Hoplias malabaricus (Bloch, 1794) from the Ctalamochita River (Córdoba, Argentina) : first evidence for southernmost populations of this species complex and comments on its biogeography - Grassi, Diego Javier (2017)
Fil: Grassi, Diego Javier. The Scripps Research Institute. Department of Molecular Therapeutics; United States.